News Portal Content Analysis of G20 Indonesia’s Presidency - Wibisono; Thoriq Mochamad (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
The background of this research is to find out how public acceptance and understanding of the news of the Indonesian Presidency in the massive G20 Summit on three news portals in the news period 14-16 November 2022. This study aims to analyze the objectivity of the Indonesian Presidency's news coverage of the G20 Summit from three news portals: cnnindonesia.com, detik.com, and kompas.com. This research was conducted quantitatively using content analysis methods using agenda setting theory, namely objectivity in journalism. Quantitative analysis is used to determine the credibility of a news with the theory of objectivity of mass media reporting using the supporting theory of Mc'Quail, McQuail's Mass Communication Theory. The data was obtained by monitoring and recording on three news portals, namely: cnnindonesia.com, kompas.com, and detik.com during the G20 Summit of the Indonesian Presidency during the news period 14-16 November 2022. The selection of these three news portals is based on the fact that the three news portals are at the forefront of news portal reporting. Content analysis research needs to be done carefully and systematically, because the results obtained can act as causes, preceding various processes, effects, and uses for specific interests. Some content analysis results are a picture of reality that can be used to describe a group or phenomenon. News objectivity is divided into three dimensions that represent, namely: public expectations (news about/comes from the public, government, politics, and media), professional opinion (types of informative news, entertainment, education), and journalistic ethics (news about Indonesia, non-Indonesia, and neutral). The score calculation results stated that the highest score for public expectations came from news from the media; the highest scores of professional opinion classify the types of informative news; and journalistic ethics state that the highest score is news about Indonesia. This research can be continued using other concepts such as news accuracy.